Metode Modified Weighted Minkowski Untuk Pengembangan Sistem Penalaran Berbasis Kasus - Edi Faizal (Jurnal Saintekom)
Knowledge acquisition process is not easy, because of the different levels of expertise even though all true. Computer experts had tried other methods to resolve the problem of the acquisition, which is known as case-based reasoning. Representation of knowledge in CBR is a collection of previous case.